Supply Chain Strategic Alignment and Integration for Competitive Advantage: a Beverage Industry Case Study - Faria, Bruna (2009)
Achieving competitiveness in the currently changing scenario of the beverage industry requires, in addition to internal efficiency of operations, the link with external processes, going beyond the traditional boundaries of the organisation. Adopting a wide Supply Chain integration perspective, including both suppliers and customers, generates significant potential benefits, however, requires the players to act collaboratively. Similarly, align Supply Chain practices to the business strategy enhance efficiency and effectiveness of operations. Both topics have been subject of significant interest. However, there are opportunities to better understand why organisations are aiming to achieve Supply Chain Integration and how Supply Chain Strategic Alignment and Integration create competitive advantage to the organisations in particular industries. Therefore, the objective of this research is to answer those questions in order to gain insights into practitioners' experiences in the beverage industry. A case study focusing on the relationship among Supply Chain Strategic Alignment and Integration and its impact on Competitive Advantage is used to explore those elements empirically. This dissertation concludes with the importance of the two Supply Chain dimensions and its impact on competitive advantage within the marketplace. Many practices have been identified as output of the case study which showed evidence of strategic alignment and internal integration, e.g. S&OP, linked KPI’s and Balanced Scorecard, whereas, opportunities were identified to foster Supply Chain external integration.